2007
DOI: 10.1007/s12028-007-0081-1
|View full text |Cite
|
Sign up to set email alerts
|

An Association of Prior Statin Use with Decreased Perihematomal Edema

Abstract: We report the association between statin use prior to ICH and decreased absolute and relative perihematomal edema. A prospective study analyzing the role of statins in perihematomal edema reduction and the resultant effect on mortality and functional outcomes following ICH is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 46 publications
(53 reference statements)
0
42
0
1
Order By: Relevance
“…20,21 A retrospective study found that prior statin use was associated with reduced perihematomal edema and improved survival in a series of patients with nontraumatic intracerebral hemorrhage. 22,23 Analysis of SPARCL data found that statin treatment was associated with an increased risk of hemorrhagic stroke in subjects with prior stroke that was independent of other factors. 1,19 Although limited by small numbers and therefore low statistical power, the current analysis found no difference in the outcomes of hemorrhagic strokes (Figure, bottom panel).…”
Section: Discussionmentioning
confidence: 99%
“…20,21 A retrospective study found that prior statin use was associated with reduced perihematomal edema and improved survival in a series of patients with nontraumatic intracerebral hemorrhage. 22,23 Analysis of SPARCL data found that statin treatment was associated with an increased risk of hemorrhagic stroke in subjects with prior stroke that was independent of other factors. 1,19 Although limited by small numbers and therefore low statistical power, the current analysis found no difference in the outcomes of hemorrhagic strokes (Figure, bottom panel).…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies on ICH patients in Johns Hopkins Hospital from 1999 to 2006 suggested association of prior statin use with decreased mortality (75) and decreased perihematomal edema (76). On the other hand, a prospective cohort study did not find association between prior use of statins and improvement in functional outcome or mortality after ICH (77).…”
Section: Statinsmentioning
confidence: 99%
“…Retrospective evaluation in a cohort of ICH patients demonstrated that prior statin use was found to be associated with decreased mortality with a greater than 12-fold odds of survival (p=0.05). The same patient population also demonstrated an association between statin use prior to ICH and decreased absolute and relative perihematomal edema at presentation [132]. There is a report of 1 small, prospective cohort of 18 patients treated with rosuvastatin compared to 57 historical controls [133].…”
Section: Anti-inflammatory Agents: Statinsmentioning
confidence: 87%